Recommendations for Sustainable Ancient DNA Research in the Global South: Voices From a New Generation of Paleogenomicists - Ávila-Arcos, Maria C.; de la Fuente Castro, Constanza; Nieves-Colón, Maria A.; Raghavan, Maanasa (Frontiers in Genetics, 2022)
Paleogenomics - the study of ancient genomes - has made significant contributions, especially to our understanding of the evolutionary history of humans. This knowledge influx has been a direct result of the coupling of next-generation sequencing with improved methods for DNA recovery and analysis of ancient samples. The appeal of ancient DNA studies in the popular media coupled with the trend for such work to be published in “high impact” journals has driven the amassing of ancestral human remains from global collections, often with limited to no engagement or involvement of local researchers and communities. This practice in the paleogenomics literature has led to limited representation of researchers from the Global South at the research design and subsequent stages. Additionally, Indigenous and descendant communities are often alienated from popular and academic narratives that both involve and impact them, sometimes adversely. While some countries have safeguards against ‘helicopter science’, such as federally regulated measures to protect their biocultural heritage, there is variable oversight in others with regard to sampling and exportation of human remains for destructive research, and differing requirements for accountability or consultation with local researchers and communities. These disparities reveal stark contrasts and gaps in regional policies that lend themselves to persistent colonial practices. While essential critiques and conversations in this sphere are taking place, these are primarily guided through the lens of US-based heritage legislation such as the Native American Graves and Protection Act (NAGPRA). In this article, we aim to expand the scope of ongoing conversations by taking into account diverse regional contexts and challenges drawing from our own research experiences in the field of paleogenomics. We emphasize that true collaborations involve knowledge sharing, capacity building, mutual respect, and equitable participation, all of which take time and the implementation of sustainable research methods; amass-and-publish strategy is simply incompatible with this ethos.